Pengaruh Fatherless terhadap Perilaku Agresif Verbal dan Nonverbal Siswa Kelas XI Di SMK X Kediri - Mentari Marwa; Wahyu Utami; Waquroti Azzahra (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The absence of a father, both physically and psychologically, has a profound impact on the emotional and social development of children, particularly increasing aggressive tendencies in those lacking the support of both parents during upbringing. This study employed a quantitative approach, utilizing questionnaires to measure levels of fatherless and student aggression. Data were collected from 60 students and analyzed using Chi-square tests to determine the relationship between fatherless and aggressive behavior. The findings revealed that the majority of students experienced moderate levels of fatherless. Validity and reliability tests of the questionnaires indicated that the data were trustworthy. The primary outcome of this research is the significant influence of father absence on both verbal and nonverbal aggressive behaviors in students. The Asymp. Sig. value in the Chi-square test was 0.001, indicating a significant relationship. The predominant form of aggressive behavior identified was verbal aggression, such as swearing and insults, while nonverbal aggressive behaviors, like hitting and pinching, were found at lower levels.